Preoperative High-Dose Methylprednisolone and Glycemic Control Early After Total Hip and Knee Arthroplasty: A Randomized, Double-Blind, Placebo-Controlled Trial. (October 2018) - Lindberg-Larsen, Viktoria; Kehlet, Henrik; Bagger, Jens; Madsbad, Sten
Abstract : BACKGROUND: To evaluate the effect of a single preoperative dose of 125 mg methylprednisolone (MP) on glycemic homeostasis early after fast-track total hip and knee arthroplasty. METHODS: One-hundred thirty-four patients undergoing elective unilateral total hip arthroplasty and total knee arthroplasty were randomized (1:1) to preoperative intravenous MP 125 mg (group MP) or isotonic saline intravenous (group C). All procedures were performed under spinal anesthesia, using a standardized multimodal analgesic regime. The primary outcome was the change in plasma glucose 2 hours postoperatively, and secondary outcomes included plasma C-peptide concentrations, homeostatic model assessment (HOMA), HOMA-IR (insulin resistance), and HOMA-B (β-cell function). Fasting blood samples were collected at baseline and 2, 6 (nonfasting), 24, and 48 hours after surgery with complete samples from 122 patients (group MP = 62, group C = 60) for analyses. RESULTS: MP patients had increased plasma glucose levels at 2 hours (adjusted mean [95% CI], 7.4 mmol·L −1 [7.2–7.5] vs 6.0 mmol·L −1 [5.9–6.2]; P = .023) and 6 hours (13.9 mmol·L −1 [13.3–14.5] vs 8.4 mmol·L −1 [7.8–9.0]; P < .001), and in plasma C-peptide 24 hours postoperatively (1675 pmol·L −1 [1573–1778] vs 1248 pmol·L −1 [1145–1351]; P < .001). An impaired insulin response was also observed in group MP as reflected by HOMA-B ( P < .001). Additionally, HOMA-IR increased 24 hours postoperatively in group MP compared to group C ( P < .001). Parameters were normalized 48 hours postoperatively. CONCLUSIONS: Preoperative administration of MP 125 mg resulted in a transient postoperative increase in plasma glucose and insulin resistance and impaired insulin secretion in response to hyperglycemia.